A Hysteresis-Based Steering Feel Model for Steer-by-Wire Systems - Arslan, M. Selcuk (HINDAWI LTD, 2017)
A mathematical model of steering feel based on a hysteresis model is proposed for Steer-by-Wire systems. The normalized Bouc-Wen hysteresis model is used to describe the steering wheel torque feedback to the driver. By modifying the mathematical model of the hysteresis model for a steering system and adding custom parameters, the availability of adjusting the shape of steering feel model for various physical and dynamic conditions increases. Addition of a term about the tire dynamics to the steering feel model renders the steering wheel torque feedback more informative about the tire road interaction. Some simulation results are presented to establish the feasibility of the proposed model. The results of hardware-in-the-loop simulations show that the model provides a realistic and informative steering feel.
Keywords: MATHEMATICAL-MODEL; DESIGN; CONTROLLER; Engineering; Mathematics